2020
DOI: 10.1200/jco.2020.38.15_suppl.e15591
|View full text |Cite
|
Sign up to set email alerts
|

The dark age of single organ screening is over: CD24 is a novel universal simple blood test for early detection of cancer.

Abstract: e15591 Background: More than 1.8 million new cancer cases are expected to be diagnosed in 2020. Only in the U.S, about 606,520 Americans are expected to die this year, which translates to about 1,660 deaths per day. However, when found early, in the asymptomatic phase, cancer is often effectively treated or even cured. The few cancer screens available today, including mammograms and colonoscopies, each look for a single type of cancer. CD24 is hardly expressed in normal cells (but to B-lymphocytes, differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…OncoSeek reported the lowest overall sensitivity across all cancer types (47.4%), 73 and CancerenD24 reported the lowest sensitivity in detecting bladder cancer (38.0%). 70 By stage, OverC and SeekInCare reported a sensitivity of 35.4% and 50.3%, 75, 77 respectively, for stage I cancer. The highest sensitivity overall came from the Carcimun-test (88.8%), 81 however, the exclusion of individuals with inflammation is noted as a disadvantage of the technology as a screening tool in the general population.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…OncoSeek reported the lowest overall sensitivity across all cancer types (47.4%), 73 and CancerenD24 reported the lowest sensitivity in detecting bladder cancer (38.0%). 70 By stage, OverC and SeekInCare reported a sensitivity of 35.4% and 50.3%, 75, 77 respectively, for stage I cancer. The highest sensitivity overall came from the Carcimun-test (88.8%), 81 however, the exclusion of individuals with inflammation is noted as a disadvantage of the technology as a screening tool in the general population.…”
Section: Resultsmentioning
confidence: 98%
“…All studies were case-control studies, except for two publications from SeekInCare 75, 76 which reported both case-control and prospective cohort studies including ‘real-world’ cohorts. A case-control study of CancerenD24, 70 reported that cancer patients and healthy controls were matched on ethnicity but did not include a description of the different ethnic groups. Ethnicity was not reported in any other study.…”
Section: Resultsmentioning
confidence: 99%